Numerical study of hydrogen/methane buoyant fires using FireFoam. (5th May 2020) - Ouyang, Yaling; He, Qize; Wang, Changjian; Shen, Zhihe
Abstract: Hydrogen/methane buoyant fires with various hydrogen volume fractions ranging from 0% to 20% were numerically studied in this paper. The modified eddy dissipation concept combustion model for multi-fuels in the large eddy simulation (LES) framework was employed for combustion, and especially the infinitely fast rate based on "global" concept was improved. Combined with the weighted sum of gray gas model for emission/absorption coefficient, the finite volume discrete ordinates model was used to compute the radiative heat transfer. The predicted centerline temperature, velocity, and flame height are in good consistence with the measured data. Furthermore, the detailed analysis was conducted on the dependency of the parameters such as centerline temperature and velocity, flame height, and soot volume fraction on hydrogen volume concentration. Highlights: The infinitely fast reaction model based on the "global" concept was improved. Effect of hydrogen volume fraction on hydrogen/methane fires was studied. Predicted results are in good agreement with experimental and theoretical values. Hydrogen addition leads to the decrease in flame height and soot fraction. Temperature and velocity are slightly affected by hydrogen volume fraction.